1985
DOI: 10.1104/pp.78.1.71
|View full text |Cite
|
Sign up to set email alerts
|

O2-Insensitive Photosynthesis in C3 Plants

Abstract: There have been a number of reports of no stimulation of photosynthesis and sometimes even an inhibition upon switching from air levels of 02 to low 02 pressure (29,31). This unusual behavior is sensitive to temperature (5, 14, 15), CO2 pressure, and light (18). In this paper, I show that as light is varied the inhibition of photosynthesis by 02 is nearly constant over a range of CO2 assimilation rates until the rate of CO2 assimilation approaches a maximum, whereupon the 02 inhibition becomes at first less se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(113 citation statements)
references
References 21 publications
5
105
0
Order By: Relevance
“…The present work also confirms the notion that the O2 enhancement of photosynthesis at CO, and light saturation (Viil et al, 1972(Viil et al, , 1977Sharkey, 1985) is related to Pi deficiency. The latter is greater in the mutant and so is the O2 enhancement.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The present work also confirms the notion that the O2 enhancement of photosynthesis at CO, and light saturation (Viil et al, 1972(Viil et al, , 1977Sharkey, 1985) is related to Pi deficiency. The latter is greater in the mutant and so is the O2 enhancement.…”
Section: Discussionsupporting
confidence: 80%
“…Cell wall C02, pM (Viil et al, 1972(Viil et al, , 1977 or 02-insensitive photosynthesis (Sharkey, 1985) at CO, saturation. Data in Figure 1 suggest that this phenomenon is related to the decline of photosynthesis with increasing CO, concentrations in low O,.…”
Section: 60mentioning
confidence: 99%
“…Our data confirm this for the lack of O 2 -inhibition at low temperature , and support an alternative explanation which is related to the concentration of inorganic phosphate (PJ in the chloroplast stroma (Sharkey, 1985). Photophosphorylation may be limited by Pj when organic phosphate levels increase due to an inbalance between CO 2 assimilation and assimilate export at high light intensity, low temperature, high p(CO 2 ) and low p(O 2 ).…”
Section: Introductionsupporting
confidence: 77%
“…However, Sharkey (1985) found that a lack of O 2 -inhibition of photosynthesis was always associated with a failure of increased CO 2 pressure to stimulate photosynthesis to the expected degree. Our data confirm this for the lack of O 2 -inhibition at low temperature , and support an alternative explanation which is related to the concentration of inorganic phosphate (PJ in the chloroplast stroma (Sharkey, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Although such a mechanism might operate during short-tem transients of source-sink mismatch, it is unlikely to be a long-tenn mechanism of feedback regulation because it would not optimize the use of the leaf's metabolic resources. A test for this kind of feedback involving failure to recycle Pi back from the chloroplast is the 0, sensitivity of net photosynthesis (Sharkey, 1985): 0,-insensitive net photosynthesis is Pi limited. In the present study net photosynthesis of both pea and soybean, whether from elevated COn or not, was highly O2 sensitive when the measured leaves were at the ages when they showed photosynthetic down-regulation (Table 111) and contained high levels of starch (Table IV).…”
Section: Discussionmentioning
confidence: 99%